2008
DOI: 10.1055/s-0031-1278274
|View full text |Cite
|
Sign up to set email alerts
|

The antihypertensive effect of arginine

Abstract: Hypertension is a leading cause of morbidity and mortality worldwide. Individuals with hypertension are at increased risk of stroke, heart disease and kidney failure. Although the etiology of essential hypertension has a genetic component, lifestyle factors such as diet play an important role. Reducing dietary salt is effective in lowering blood pressure in salt-sensitive individuals. Insulin resistance and altered glucose metabolism are common features of hypertension in humans and animal models, with or with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 215 publications
(304 reference statements)
2
28
0
6
Order By: Relevance
“…Our finding is consistent with a previous report which indicated that L-arginine levels are reduced in Pre-eclampsia (PE), a syndrome of pregnancy-induced hypertension [30]. Arginine deficiency or lack of availability, and changes in arginine metabolism, has the potential to contribute to increased blood pressure and endothelial cell dysfunction [31].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our finding is consistent with a previous report which indicated that L-arginine levels are reduced in Pre-eclampsia (PE), a syndrome of pregnancy-induced hypertension [30]. Arginine deficiency or lack of availability, and changes in arginine metabolism, has the potential to contribute to increased blood pressure and endothelial cell dysfunction [31].…”
Section: Discussionsupporting
confidence: 93%
“…Although the etiology of hypertension has a genetic component, lifestyle factors such as diet play an important role. A diet rich in protein containing the semi-essential amino acid, arginine, and arginine treatment, lowers blood pressure in humans and in animal models [31]. The Dietary Approaches to Stop Hypertension (DASH) study demonstrated that the DASH diet, rich in vegetables, fruits and low-fat dairy products; low in fat; and including whole grains, poultry, fish and nuts, lowered blood pressures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Furthermore, high content of antioxidants and arginine amino acid in the DASH diet may improve metabolic status through decreased NADPH oxidase activity 19 and reduced angiotensin II levels. 20 Despite these findings, to our knowledge, data on effects of the DASH diet on weight loss, AMH and metabolic profiles in women with PCOS is limited. We hypothesized that the DASH diet might benefit in patients with PCOS to improve their metabolic profiles.…”
mentioning
confidence: 99%
“…Of note, L-arginine is a semi-essential amino acid, which is obtained from natural dietary sources and can be produced endogenously in various organs [11]. L-arginine plays a vital role in various physiological functions and, prominently, in maintaining vascular homeostasis [10].…”
Section: Introductionmentioning
confidence: 99%